A study on distribution and gender wise predilection of lip print pattern - Timsinha, Sidarth; Kar, Suvarna Manjari (Asian Journal of Medical Sciences, 2019)
Background: Lip prints are considered as very useful and are to be important forms of transfer evidence like finger prints. Studies have shown that even lip prints are unique for an individual and hence have the potential for personal identification. Aims and Objectives: To correlate the distribution of lip print pattern and its gender wise predominance. Material and Methods: The study comprised of 100 Nepalese medical students (50 males; 50 females). A photographic method was adopted rather than the old traditional lipstick method. The photographed lip prints were transferred into a computer to identify the character/lip print pattern. Statistical analysis was done using the SPSS (version 23.0) software package and Chi-square test was applied to evaluate the existence of correlation of lip print pattern with gender. Results: Type- II lip print pattern was frequently observed in all the four quadrants of both the sexes. This was followed by in order Type-I’>Type-I> Type-IV and Type-III lip patterns. There was a difference in gender wise distribution of lip prints. Conclusion: Further specific population based and gender specific studies on lip prints with larger sample size are required for comparison of lip prints with gender, so that a database could be created and used for representing sex differentiation.